Etika Lingkungan dan Kearifan Lokal: Menjaga Harmoni Alam di Setu Babakan - Anita Khumairoh; Artiwi Budiarti; Diva Putri Vania; Handini Widya Mulya Astiti; Rizaldi Khairun Nuzul; Faridah Hamidah Iswahyudi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Indonesia faces significant challenges in maintaining environmental ethics amid rapid economic growth and urbanization. Environmental degradation, such as deforestation, water pollution, and poor waste management, reflects a widespread lack of ecological awareness. However, local wisdom offers an alternative approach to environmental sustainability. This study aims to describe the forms of environmental ethics embedded in the local wisdom of the Betawi community in the Betawi Cultural Village of Setu Babakan, South Jakarta. Using a descriptive qualitative method, the research explores cultural practices that support environmental preservation, including the use of home gardens, reverence for nature, and community-based waste management. The findings show that the Setu Babakan community applies ecological principles through traditions, customs, and active participation in environmental care. Moreover, synergy between the government, local communities, and the tourism sector contributes to developing an area that not only preserves Betawi culture but also maintains ecological balance. These findings highlight the importance of integrating local cultural values into environmental policy as a pathway toward sustainable development.